Baseline characteristics and outcomes of children with cancer in the English‐speaking Caribbean: A multinational retrospective cohort. Issue 12 (9th August 2018) - Gibson, T. N.; Beeput, S.; Gaspard, J.; George, C.; Gibson, D.; Jackson, N.; Leandre‐Broome, V.; Palmer‐Mitchell, N.; Alexis, C.; Bird‐Compton, J.; Bodkyn, C.; Boyle, R.; et al.
Abstract: Background: English‐speaking Caribbean (ESC) childhood cancer outcomes are unknown. Procedure: Through the SickKids‐Caribbean Initiative (SCI), we established a multicenter childhood cancer database across seven centers in six ESC countries. Data managers entered patient demographics, disease, treatment, and outcome data. Data collection commenced in 2013, with retrospective collection to 2011 and subsequent prospective collection. Results: A total of 367 children were diagnosed between 2011 and 2015 with a median age of 5.7 years (interquartile range 2.9–10.6 years). One hundred thirty (35.4%) patients were diagnosed with leukemia, 30 (8.2%) with lymphoma, and 149 (40.6%) with solid tumors. A relative paucity of children with brain tumors was seen ( N = 58, 15.8%). Two‐year event‐free survival (EFS) for the cohort was 48.5% ± 3.2%; 2‐year overall survival (OS) was 55.1% ± 3.1%. Children with acute lymphoblastic leukemia (ALL) and Wilms tumor (WT) experienced better 2‐year EFS (62.1% ± 6.4% and 66.7% ± 10.1%), while dismal outcomes were seen in children with acute myeloid leukemia (AML; 22.7 ± 9.6%), rhabdomyosarcoma (21.0% ± 17.0%), and medulloblastoma (21.4% ± 17.8%). Of 108 deaths with known cause, 58 (53.7%) were attributed to disease and 50 (46.3%) to treatment complications. Death within 60 days of diagnosis was relatively common in acute leukemia [13/98 (13.3%) ALL, 8/26 (30.8%) AML]. Despite this, traditional prognosticators adversely impacted outcome in ALL, including higher age, higher white blood cell count, and T‐cell lineage. Conclusions: ESC childhood cancer outcomes are significantly inferior to high‐income country outcomes. Based on these data, interventions for improving supportive care and modifying treatment protocols are under way. Continued data collection will allow evaluation of interventions and ensure maximal outcome improvements.